1999
DOI: 10.1159/000016515
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Carbonic Anhydrase Isoenzyme VI Is Located in the Human Enamel Pellicle

Abstract: Salivary carbonic anhydrase (CA VI) appears to protect teeth from caries via mechanisms other than direct regulation of salivary pH and buffering capacity. To elucidate whether CA VI acts in the local microenvironment of the tooth surface, we studied the location and activity of the enzyme in the human enamel pellicle. The study was performed using a specific rabbit antiserum to human CA VI in conjunction with immunostaining and immunoblot techniques. CA activity was demonstrated using a histochemical stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
2
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 12 publications
2
64
2
3
Order By: Relevance
“…14 Bicarbonate ions can neutralize lactic and acetic acids produced by plaque bacteria and reduce demineralization. CAVI can adsorbs to the crystals of hydroxyapatite of enamel; 15 it is present in the enamel pellicle 16 and in dental biofilm. 17 Salivary buffer capacity seems to be a determinant factor on dental erosion, which is becoming a major dental problem in both children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…14 Bicarbonate ions can neutralize lactic and acetic acids produced by plaque bacteria and reduce demineralization. CAVI can adsorbs to the crystals of hydroxyapatite of enamel; 15 it is present in the enamel pellicle 16 and in dental biofilm. 17 Salivary buffer capacity seems to be a determinant factor on dental erosion, which is becoming a major dental problem in both children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the salivary buffer effect based on proteins has produced controversial results. In general the effect has been regarded as insignificant, or at least of minor importance, although data suggesting an alternative conclusion have also been presented (Leung, 1961;Izutsu & Madden, 1978 The existence of CA activity in human saliva has been known for 60 years (Becks & Wainwright, 1939), but until recently only a few studies had been carried out on the physiological role of salivary CA (Rapp, 1946;Szab o, 1974;Parkkila et al 1997;Kivel a et al 1997aKivel a et al , 1999Leinonen et al 1999). The ovine salivary CA isoenzyme expressed in the parotid gland was described in 1979 by Fernley et al The enzyme was purified from human saliva by Murakami & Sly (1987), and designated CA VI.…”
mentioning
confidence: 99%
“…It is also thought to prevent calculus formation on the dental surfaces by controlling the precipitation of calcium phosphate from supersaturated saliva (Hay & Moreno, 1989). Recent research has indicated that CA VI binds to the enamel pellicle and retains its enzyme activity on dental surfaces (Leinonen et al 1999). In the enamel pellicle, CA VI is located at the optimal site to catalyse the conversion of salivary bicarbonate and microbe-delivered hydrogen ions to carbon dioxide and water (Fig.…”
mentioning
confidence: 99%
“…With regard to the cytosolic CA isozymes, Asari et al [4] have already investigated well-known CA isozymes (CA-I, CA-II and CA-III) in bovine salivary glands and alimentary canal. The secretory CA-VI accelerates the neutralization of excess organic acids produced by microbial flora on dental and epithelial surfaces in the oral cavity and it forms a mutually complementary system with cytosolic CA for pH regulation in the upper alimentary canal [17,26]. CA-VI may be used for the control of pH and ion balance at the ruminant upper digestive tract in association with other CA isozymes.…”
Section: Resultsmentioning
confidence: 99%